Principles of differentiation of pension relations: some aspects of the theory of pension law - Нижник, Ніна Романівна; Гуменюк, Ірина Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The article analyzes the foundation of differentiation of pension relations’ legal regulation, clarifies the principles of solidarity and differentiation. We investigate the possibility of introducing common principles of calculating pensions for persons whose pensions are provided according to the norms of a special law. It is concluded that implementation of common principles of calculating pensions for persons, whose professional activity is regulated by special legislature, is possible if the size of these pensions is calculated according to the first level of pension system which is based on solidarity, with simultaneous settlement of additional pension provision in the frames of the second level of pension system by contributions to individual retirement accounts. The author mentions the other way to solve this problem and states that it is a refusal of “state public” model of official relations regulation. This idea deserves attention as a major amount of state official’s functions belong to the sphere of labor law legal regulating.